The Reflection on Architectural Discourse of 1920’s: Musical Urbanism between Radicalism and Tradition - Edler, Florian (Selected Topics in Humanities and Social Sciences Vol. 2, 2021)
Various compositions evolved in the aftermath of World War I that addressed the phenomenon of the modern city by translating the clamorous sounds of urban surroundings and expressing them artistically in the medium of music. Since the rendering of poetic and esoteric moods unrelated to practical life was largely considered outdated, musical preoccupation with modern architecture mostly concerned social aspects, such as people’s circumstances, their emotional rootedness to bygone conditions, and the search for orientation in an environment characterized by technology. There are clear parallels with contemporary architectural debates in which tension between modernism and traditionalism also played a key role. This article compares different country-specific concepts of a musical urbanism, which finds expression in compositional reflections on certain aspects of modern urban architecture and urban life.